Faktor-Faktor yang Berhubungan dengan Kejadian Berat Badan Lahir Rendah - Reflita Reflita; Hasni Mastian (NERS Jurnal Keperawatan)
Data birth in January-November 2009 the hospital Dr .M.Jamil Padang as many as 699 babies who had low birth weight cases as many as 289 (41.34%).The purpose of this study was to determine the factors associated with the incidence of LBW in dr.M Djamil hospital Padang. This research is Analytical Descriptive cross-sectional design. Its sampel werw 237 people data. Data used in this research was secondary data, then the data were analyzed using chi-square and logistic regression.